THE LAW ABOUT SECURITIES MARKET AS A LAW ABOUT FINANCE MARKETS - Vladimir A. Galanov; Aleхandra V. Galanova (Вестник Российского экономического университета имени Г. В. Плеханова)
The development of the Law about securities market is taking place not only in the direction of deeper regulation of the given market itself but  also in the direction of broader covering of other finance markets with  finance tools which differ from securities and covering other trade and  credit operations apart from operations dealing with issuance and  circulation of issue securities. This situation is justified due to relative  underdevelopment of certain finance markets in Russia. The authors  show that in order to develop these markets it is necessary to design  their independent regulation both in the field of normative documents and in administrative regulation.